ANALISIS PENGUKURAN WAKTU KERJA DALAM MENENTUKAN WAKTU STANDAR DI PT. FLEXTRONIC TECHNOLOGY INDONESIA - Yunitia; Anggia Arista (LPPM Universitas Putera Batam, 2024)
This research aims to measure working time during the Print Circuit Board (PCB) inspection process at PT. Flextronic Technology Indonesia and determine optimal time standards to increase work productivity. The method used is a time study by taking samples from one operator in 30 observations for 10 processes. The measurement results show that the standard PCB inspection time is 64 units in 1 hour. Determining standard time takes into account the adjustment factors and allowances required in the work process. The results of this research indicate that the PCB inspection process at PT Flextronic Technology Indonesia is a critical stage in electronics manufacturing to ensure that PCBs meet predetermined specifications and quality standards. Process time measurements were carried out using the time study method and a time standard of 64 units per hour or 508 units per shift was obtained to complete one PCB inspection process.